Comprehensive molecular characterizations of stage I–III lung adenocarcinoma with tumor spread through air spaces - Ye, Ronghao; Yu, Yongfeng; Zhao, Ruiying; Han, Yuchen; Lu, Shun (Frontiers in Genetics, 2023)
Abstract Purpose: The aim of this study is to investigate integrative genomic spectra of stage I-III lung adenocarcinoma with tumor spread through air spaces (STAS). Methods: We retrospectively identified 442 surgically resected lung adenocarcinoma patients of pathological stage I-III in Shanghai Chest Hospital from January 2018 to February 2021. Surgically resected tissues were undergone next-generation sequencing (NGS) with a panel of 68 lung cancer‐related genes to profile comprehensive molecular characterizations. Results: A total of 442 cases were analyzed, including 221 (50%) STAS-positive (SP) and 221 (50%) STAS-negative (SN) lung adenocarcinoma patients. 440 cases (99.6%) were positive for the overall mutational spectrum, and the higher mutational genes were EGFR, TP53, KRAS, ALK, SMAD4, and ERBB2 (62%, 42%, 14%, 10%, 7%, and 7%, respectively). Compared with SN population, significantly lower EGFR alteration in the single nucleotide variant (SNV) mutation spectrum (52.5% vs. 69.7%, P < 0.001) and significantly higher TP53 alteration were suggested in the SP population (49.8% vs. 34.8%, P = 0.002). EGFR L858R missense mutation (19.5% vs. 37.6%, P < 0.001) and ERBB2 exon 20 indel mutation (1.8% vs. 5.9%, P = 0.045) were more frequent in SP population. The detection rate of ALK fusion rearrangements in the SP population was significantly higher than that in the SN population (13.1% vs. 2.3%, P < 0.001). In the analysis of signaling pathways, no significant difference was discovered between SP and SN patients. No difference in 1-year DFS was observed between SP and SN patients in this study. Conclusions: Significant differences exist in stage I-III lung adenocarcinoma patients of STAS in molecular characterizations.